Study the Development and Management of the Souphanouvong University Football Club - Chitdeela , Chittaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to study the development conditions and management of the football club at Souphanouvong University. Data were collected from a sample group of 100 participants. The research instrument used was a questionnaire, and the data were analyzed using descriptive statistics to determine the mean (X̄) and standard deviation (SD).The research results showed that the football club has a well-structured organizational system for its operations, which is at a high level (X̄ = 4.00, SD = 1.36). The promotion of student participation in activities and the regular organization of competitions are also at a high level (X̄ = 3.80, SD = 0.92). The club has strategies for participating in both internal and external competitions, achieving success and building its reputation, with satisfaction at a high level (X̄ = 3.70, SD = 0.71).The club has its own training facilities, sufficient personnel, and collaboration with external institutions or communities to seek funding support. The administrators are experienced and professional, all of which are at a high level (X̄ = 3.65, SD = 0.79). Strategic planning for future club development is also at a high level (X̄ = 3.55, SD = 0.67).However, the application of sports science, medical care, and athlete health management is at a moderate level (X̄ = 3.15, SD = 1.06). Training facilities are not yet up to standard and are insufficient to meet needs, and government budget support is still low (X̄ = 3.20, SD = 1.36). Budget allocation for renovation, development of sports fields, and equipment is also at a moderate level (X̄ = 3.15, SD = 0.89). Training equipment is insufficient and not up to standard, at a moderate level (X̄ = 2.95, SD = 0.96). From the research findings, it is evident that the football club of Souphanouvong University needs to develop clear plans and establish development strategies to meet standards and reach an international level.